The Law of Judiciary Power Synergizing the Positivism and Historicism - Christiani Widowati; Indira Retno Aryatie (Fakultas Hukum Universitas Hang Tuah, 2018)
Judiciary Power. Indonesia applies Civil Law System; that considers legislation as the primary legal source. Preferring legislation as a legal source is one characteristic of positivism. The Civil Law System, however, mentions that judges are obligated to see the values in society if the legislation does not set for that. It implicitly refers to societal law, including common Law. Taking the common law as a legal source is the characteristic of historicism as well; mentioning that the soul of a nation (volkgeist) derives from the values living in society. Basically, these two schools are contradictory to one another in their perspective of law. Positivism sees that state-made law is the only applied law. The law of Judiciary Power synergies between these two schools and takes a common low as a legal source for judges to make a decision.